2019
DOI: 10.14309/ctg.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Racial/Ethnic Differences of Colorectal Cancer Among Adolescents and Young Adults

Abstract: OBJECTIVES: Despite overall reductions in colorectal cancer burden, incidence rates continue to rise among younger patients, and causes remain unknown. We examined differences in clinicopathologic and racial/ethnic characteristics within the adolescent and young adult (AYA) population diagnosed with colorectal cancer in the United States. METHODS: Using the National Cancer Institute's Surveillance, Epidemiology, and End Results program data, we identified individuals diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
3
24
0
2
Order By: Relevance
“…Moreover, as alpelisib—a PIK3CA inhibitor—became FDA-approved last year for PIK3CA -altered, hormone receptor–positive advanced breast cancer, 40 this study reveals that 12% of early-onset AC cases could potentially benefit from targeting this variation and merits further study. Moreover, as studies have posited that adolescents and young adults (AYAs; age 18-39 years) harbor a distinct biology of cancer 41 , 42 , 43 ; additional investigation of variation patterns within the AYA population are needed in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as alpelisib—a PIK3CA inhibitor—became FDA-approved last year for PIK3CA -altered, hormone receptor–positive advanced breast cancer, 40 this study reveals that 12% of early-onset AC cases could potentially benefit from targeting this variation and merits further study. Moreover, as studies have posited that adolescents and young adults (AYAs; age 18-39 years) harbor a distinct biology of cancer 41 , 42 , 43 ; additional investigation of variation patterns within the AYA population are needed in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…It is universally acknowledged that the death and incidence rate of some tumors are often related with race/ethinicity, [ 22 25 ] therefore, in our study, we also discuss whether race/ethnicity is associated with the survival of TSCC, and discovers that race/ethnicity does not have any correlation with the overall survival. The Gad MM's study has proposed that pancreatic adenocarcinoma is associated with race and confirmed the annual increasing mortality rate of Asians, which does not bear any correlation with age and stage.…”
Section: Discussionmentioning
confidence: 87%
“…Colorectal cancer (CRC) causes significant morbidity and mortality throughout the world. CRC rates are increasing in young adults at an alarming rate which may be due to lifestyle and genetic factors (62). Hence, new therapeutic agents are urgently needed to improve outcomes for the increasing number of individuals who will be diagnosed with CRC.…”
Section: Discussionmentioning
confidence: 99%